PENGARUH KARAKTERISTIK KOMITE AUDIT TERHADAP PENGUNGKAPAN CSR DENGAN KEBERADAAN MANAJEMEN RISIKO SEBAGAI VARIABEL INTERVENING - Farah Nofri Pudjianti; Imam Ghozali (Diponegoro Journal of Accounting, 2021)
This study aims to examine and analyze the effect of audit committee on corporate social responsibility disclosure with the existence of risk management as an intervening variable. The independent variable in this study is audit committee that consist of independence, size, meeting, and financial expertise. Corporate social responsibility (CSR) disclosure used as an dependent variable. The sample in this study is non-financial companies which listed on Indonesian Stock Exchange (IDX) on 2017-2018 with the total sample of 684 companies. This study examine the relationship between independent variable, intervening variable, and dependent variable by using partial least squares structural equation modeling (PLS-SEM) analysis. The result shows that meeting of audit committee, size of audit committee and risk management has positive significant to CSR disclosure. Meanwhile, independence has no significant and financial expertise of audit committee has negative effect to CSR disclosure. The other result of this study shows that meeting and size of audit committee has positive significant to CSR disclosure with the existence of risk management as an intervening variable.